Elevating Oncological Care through Robust Electronic Medical Record Systems - Lamichhane, Nirmal (Nepalese Journal of Cancer, 2025)
Cancer care today is defined by complexity, precision, and multidisciplinary collaboration. From genetic and molecular diagnostics to surgery, radiotherapy, systemic therapy, and survivorship, oncological practice generates vast quantities of heterogeneous data over extended time spans. As health systems pursue greater efficiency, quality, and patient safety, Electronic Medical Records (EMRs) emerge as a cornerstone for modernizing oncology. But realising their potential demands not only technology, but thoughtful design, governance, and evidence-based integration.